It's Time to Get It Right: Problem-Solving in the First-Year Curriculum - Bobbi McAdoo; Sharon Press; Chelsea Griffin (Washington University Journal of Law & Policy, 2012)
In the Fall of 2010, two of the authors taught a newly required first-year course: Practice, Problem-Solving and Professionalism, or P3 as it has come to be known at Hamline University School of Law (HUSL). In this Article, we will use the P3 course as a case study in legal education curricular reform. We contend that the problem-solving emphasis of the course and its placement in the first-year curriculum responds elegantly to the various calls for legal education reform over the last few decades. Moreover, the course is fairly easily replicated, even in large first-year classes. Most importantly, we believe it should replace separate Alternative Dispute Resolution (ADR) courses which have proliferated in law school curricula. We do not advocate for the original Missouri model of total integration of ADR concepts into all first-year courses for both pedagogical and practical reasons. First, we believe that model is viable only for law schools with someone on the faculty as singularly focused as Riskin, and with grant money available to implement the model. Second, the pedagogies of using simulations and even ―adventure learning appropriate to a problem-solving course are not a good fit for most doctrinal professors. Third, the amount of coordination among and between very independent law faculty members required by a fully integrated model is simply too overwhelming. Even Missouri has moved to requiring Lawyering: Problem-Solving and Dispute Resolution as a first-year course, instead of its original path-breaking approach in the nineties. Part II of this Article briefly reviews some reforms in legal practice and legal education as they relate to ADR and problem-solving. Part III details the institutional genesis of the P3 course at Hamline. Part IV explains the actual design and implementation of the P3 course. In Part V, we critique the course and provide details for the revised spring 2012 iteration. Finally, in Part VI, we reiterate our support for a problem-solving course in the first-year legal curriculum.
Keywords: Law schools – courses; Legal education reforms; Hamline University School of Law; Legal education – innovative approaches; Alternative dispute resolution (ADR); Lawyering; Law students; The MacCrate Report; The Carnegie Report; Practice; Problem-Solving and Professionalism course (P3)